Reunderstanding the reaction mechanism of aqueous Zn–Mn batteries with sulfate electrolytes: role of the zinc sulfate hydroxide - Chen, Hao (2022)
Rechargeable aqueous Zn-Mn batteries have garnered extensive attention for next-generation high-safety energy storage. However, the charge-storage chemistry of Zn-Mn batteries remains controversial. Prevailing mechanisms include conversion reaction and cation (de)intercalation in mild acid or neutral electrolytes, and a MnO2 /Mn2+ dissolution-deposition reaction in strong acidic electrolytes. Herein, a Zn4 SO4 ·(OH)6 ·xH2 O (ZSH)-assisted deposition-dissolution model is proposed to elucidate the reaction mechanism and capacity origin in Zn-Mn batteries based on mild acidic sulfate electrolytes. In this new model, the reversible capacity originates from a reversible conversion reaction between ZSH and Znx MnO(OH)2 nanosheets in which the MnO2 initiates the formation of ZSH but contributes negligibly to the apparent capacity. The role of ZSH in this new model is confirmed by a series of operando characterizations and by constructing Zn batteries using other cathode materials (including ZSH, ZnO, MgO, and CaO). This research may refresh the understanding of the most promising Zn-Mn batteries and guide the design of high-capacity aqueous Zn batteries.